Data set. - Belachew Tekleyohannes Wogayehu (19470257) (2025)
Introduction The prevalent condition known as hand eczema has been associated with substantial decreased quality of life, as well as considerable social and occupational expenses. Even though hairdressing is a significant source of wealth, it is linked to several kinds of medical problems mainly skin conditions. Limited studies conducted in Ethiopia to assess self-reported prevalence of hand eczema and associated factors. Objective This study aims to assess self-reported prevalence of hand eczema and associated factors among hairdressers of Debre Berhan city. Methods A cross-sectional study was conducted among 435 hairdressers of Debre Berhan city in North Eastern Ethiopia from January 10 to February 20, 2025. A simple random sampling technique was used to select hair dressers. Data was collected using a structured questionnaire adapted from Nordic occupational skin questionnaire and observational checklist through face to face interview and observation. Multivariable binary logistic regression was employed to identify associated factors of hand eczema. Results Prevalence of hand eczema among hairdressers of Debre Berhan city was 56.9%. Poor knowledge (AOR = 2.89, 95% CI: 1.199–4.963), not utilizing personal protective equipment consistently over the years (AOR = 3.8, 95% CI: 2.183–7.012), low hand washing frequency per day (AOR = 3.4, 95% CI: 1.399–6.433) and not taking OHS training (AOR = 4.8, 95% CI: 2.617–8.709) were identified factors of hand eczema. Conclusions Prevalence of hand eczema among hair dressers in Debre Berhan city was high. Poor knowledge, not utilizing personal protective equipment consistently over the years, low hand washing frequency per day and not taking OHS training were identified factors. Hair dressers should utilize proper type of personal protective equipment before starting any activities in the work place. Inclusion of hand eczema education in Technical and Vocational Educational and Training (TVET) or policy-level interventions would enhance occupational health awareness, early prevention strategies and long-term skin protection practices among hairdressers.